An Efficient Hybrid MoM/FEM Method for Analyzing the Enclosures With Apertures - SİBEL YENİKAYA (Pamukkale University Journal of Engineering Sciences, 2011)
In this paper a hybrid formulation is presented which combines edge-based vector finite method (FEM) and Method of Moments (MoM) in frequency domain to predict electromagnetic field distribution inside an enclosure with aperture. While MoM is used for solving the surface integrals related with the aperture field components via equivalent surface currents, FEM is used for solving electromagnetic fields inside of the enclosure. Numerical results for shielding effectiveness and electrical energy of enclosure with aperture are calculated by the hybrid method and they are presented and validated with the existing literature. Then the method is applied to different enclosures with different aperture sizes.